2021
DOI: 10.7759/cureus.14097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anatomical Locations of Stroke Events From Computed Tomography Scan Examinations in a Tertiary Facility in Ghana

Abstract: IntroductionStroke events are leading causes of mortalities globally and currently increasing alarmingly in low-and middle-income nations including Ghana, thus overburdening national healthcare delivery sectors. This trend is predicted to ultimately have an impact on the socio-economic development of these countries, thus gaining the attention of policy-makers and implementers. This study was therefore conducted to evaluate the anatomical locations of stroke events from CT scan examinations and the possibly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…al, have stated in their study that basal ganglia region was most common site of ICH followed by patietal lobe, frontal lobe, temporal lobe and cerebellum in descending order. 10 Basal ganglia region that includes putamen, caudate and thalamus were the most common site of bleeding in our study as well. Study on prevalence of thalamic hematoma have reported ranging from 6% in series of Juvela et al 11 to 15.7% in series of tatu et al 12 Kumral et al have reported prevalence of thalamic hematoma as 25.6%.…”
Section: Resultssupporting
confidence: 57%
“…al, have stated in their study that basal ganglia region was most common site of ICH followed by patietal lobe, frontal lobe, temporal lobe and cerebellum in descending order. 10 Basal ganglia region that includes putamen, caudate and thalamus were the most common site of bleeding in our study as well. Study on prevalence of thalamic hematoma have reported ranging from 6% in series of Juvela et al 11 to 15.7% in series of tatu et al 12 Kumral et al have reported prevalence of thalamic hematoma as 25.6%.…”
Section: Resultssupporting
confidence: 57%
“…Strokes are generally known to be a significant cause of morbidity and mortality in the world and Africa in particular. Its incidence has been reported to be increasing with increasing age and as the years go by [ 16 , 21 ]. Therefore, the findings from this current study emphasize the essence of knowing the radiological features of CT scan for SICH in order to enable quick and accurate diagnosis, as the management of such events depends on how early the diagnosis is made.…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of CT in 1972, has significantly improved the accuracy and diagnosis of intracranial hemorrhage, and has become the neuro-imaging modality of choice in the assessment of SICH [ 2 , 12 , 13 ]. Even though CT scan has been reported in a recent study in Ghana as one of the most available imaging modalities in radiological practices and hence the most employed modality for neuroimaging, there are some challenges like relatively high cost, frequent power failures and few others which may end up delaying early detection of SICH [ 14 - 16 ]. Therefore, we aimed at analyzing the CT scan patterns in patients with spontaneous intracranial hemorrhage in a tertiary care hospital located in the Central Region of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Others cover a host of subjects ranging from goiter 37 , alloimmunization 38 , kidney diseases 39 and trauma 40 . The next set of papers, is on sexual reproductive health [41][42][43][44][45][46][47][48][49][50][51][52] . The rest are on nutrition [53][54][55] , mental health [56][57][58] and a couple of hybrid issues [59][60][61][62] .…”
mentioning
confidence: 99%